12g-5+g(3-4)=

Simple and best practice solution for 12g-5+g(3-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12g-5+g(3-4)= equation:


Simplifying
12g + -5 + g(3 + -4) = 0

Combine like terms: 3 + -4 = -1
12g + -5 + g(-1) = 0

Reorder the terms for easier multiplication:
12g + -5 + -1g = 0

Reorder the terms:
-5 + 12g + -1g = 0

Combine like terms: 12g + -1g = 11g
-5 + 11g = 0

Solving
-5 + 11g = 0

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 11g = 0 + 5

Combine like terms: -5 + 5 = 0
0 + 11g = 0 + 5
11g = 0 + 5

Combine like terms: 0 + 5 = 5
11g = 5

Divide each side by '11'.
g = 0.4545454545

Simplifying
g = 0.4545454545

See similar equations:

| 168=-8x | | 2x^2+9x=4x+42 | | 1+2nx=3 | | 3x+19=-10 | | 8xy^2+3x^2y=35 | | 0=4x^2-4x-5x^2 | | 10a^2-43a+28=0 | | -5u-w=u+4w | | sqrtx-4=7 | | 10x+2x+13=146 | | 27x+12y+39= | | 7q+14=-55 | | -4(2-y+3y)=3(y-4) | | 10r+11=-2r-1 | | 2x+5(-4x-8)=-184 | | -8p+13=45 | | b+17=-41 | | 14x-13+5x+10+8x+11+10x+5=180 | | 378=-21b | | x-75=-9 | | 2(e-8)+9=5(e+2)-3e-17 | | 378=21b | | 3y+12=3 | | 20x-6-13x+4=23x-8-16x+12 | | 3(x+2)-y+2=14 | | 1nx+1nx(x+1)=3 | | 1.8=5cos(pi*t) | | y-1=1/4)x=2) | | 2x+13=10x+126 | | x=48+0.17y | | -64=2y | | 5/6y-2=8 |

Equations solver categories